2021
DOI: 10.3389/fgene.2021.699420
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of miRNAs and Development of Heat-Responsive miRNA-SSR Markers for Characterization of Wheat Germplasm for Terminal Heat Tolerance Breeding

Abstract: A large proportion of the Asian population fulfills their energy requirements from wheat (Triticum aestivum L.). Wheat quality and yield are critically affected by the terminal heat stress across the globe. It affects approximately 40% of the wheat-cultivating regions of the world. Therefore, there is a critical need to develop improved terminal heat-tolerant wheat varieties. Marker-assisted breeding with genic simple sequence repeats (SSR) markers have been used for developing terminal heat-tolerant wheat var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…A variety of DNA based markers ''popularly also known as molecular markers'' have become available and are being used in crop improvement programs world-wide (Gupta et al 2008;Mir et al 2013a;Mir and Varshney 2013;Gupta et al 2013;Kumar et al 2021). Some of the most important type of markers still popular for molecular breeding programs includes SSR markers, SNP markers, Array-based markers and recently emerged microRNA based markers (Gupta et al 2008;Tyagi et al 2019;Tyagi et al 2021;Sihag et al 2021). In chickpea, a variety of molecular markers including AFLPs, RAPDs, SSRs have been already used to unravel and understand the genetic diversity available in chickpea (Talebi et al 2008a, b;Saeed et al 2011;Keneni et al 2012;Ghaffari et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A variety of DNA based markers ''popularly also known as molecular markers'' have become available and are being used in crop improvement programs world-wide (Gupta et al 2008;Mir et al 2013a;Mir and Varshney 2013;Gupta et al 2013;Kumar et al 2021). Some of the most important type of markers still popular for molecular breeding programs includes SSR markers, SNP markers, Array-based markers and recently emerged microRNA based markers (Gupta et al 2008;Tyagi et al 2019;Tyagi et al 2021;Sihag et al 2021). In chickpea, a variety of molecular markers including AFLPs, RAPDs, SSRs have been already used to unravel and understand the genetic diversity available in chickpea (Talebi et al 2008a, b;Saeed et al 2011;Keneni et al 2012;Ghaffari et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the influence of post-transcriptional regulation through non-coding RNAs (miRNA, siRNA, lncRNA) is well known. It has been reported that the target genes of such RNAs are generally those with ontologies related to cell wall architecture, ROS regulation, and the development of the next phase, among others [40,41]. Similarly, epigenetic mechanisms have been found to be involved in the response to thermal stress, such as DNA methylation, histone modifications, and chromatin remodeling [42].…”
Section: Ros Regulation and Detoxificationmentioning
confidence: 99%
“…The miR408 overexpression results plantacyanin transcript repression to regulate DREB and other drought responsive genes [ 186 ]. This tool can largely aid in future breeding programmes for various biotic and abiotic stresses in legumes as in wheat 70 miRNA based SSR markers have been identified and validated on a set of 20 terminal heat-tolerant and heat-susceptible genotypes for developing heat tolerant cultivars through marker assisted selection [ 215 ].…”
Section: Genomics Interventionsmentioning
confidence: 99%